2013
DOI: 10.17796/jcpd.37.4.8q77717841781527
|View full text |Cite
|
Sign up to set email alerts
|

Enamel Defects in the Primary Dentition of Preterm and Full Term Children

Abstract: Aim: This study compared enamel defects in children born prematurely and at term. Method: 96 children born at term (G1), and with 96 children born prematurely (G2) were studied. Results: A higher prevalence of enamel defects was found in the premature group, with a predominance of hypoplasia. In G1, 64 teeth displayed enamel defects (51 opacities and 13 hypoplasias). In G2, 110 defective teeth were found, (29 opacities and 81 hypoplasias). A significant correlation was found between very low birth weight (VLBW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
0
9
0
2
Order By: Relevance
“…For example, Skinner et al (2014) revealed that localized enamel defects occur more frequently in pigs that are sick at the time of death and that they co-occur with both infection and poor growth. Numerous studies have found that low birth weight and preterm birth are associated with increased risk of enamel hypoplasia and that maternal health plays a role in enamel hypoplasia formation in children (Gravina et al 2013;Jacobsen et al 2014;Masumo et al 2013;Silva-Sousa et al 2003;Souza et al 2012). Research among living people indicates that children with enamel hypoplasia are of significantly shorter stature than those without them (Lukacs et al 2001).…”
Section: Advances In Our Understanding Of Lesion-formation Processesmentioning
confidence: 99%
“…For example, Skinner et al (2014) revealed that localized enamel defects occur more frequently in pigs that are sick at the time of death and that they co-occur with both infection and poor growth. Numerous studies have found that low birth weight and preterm birth are associated with increased risk of enamel hypoplasia and that maternal health plays a role in enamel hypoplasia formation in children (Gravina et al 2013;Jacobsen et al 2014;Masumo et al 2013;Silva-Sousa et al 2003;Souza et al 2012). Research among living people indicates that children with enamel hypoplasia are of significantly shorter stature than those without them (Lukacs et al 2001).…”
Section: Advances In Our Understanding Of Lesion-formation Processesmentioning
confidence: 99%
“…18 Gravina ve ark. 23 prematüre doğanlarda en fazla süt kesici ve kanin dişlerde, normal doğum yaşında dünyaya gelenlerde ise süt molar ve kanin dişlerde GMD izlendiğini saptamıştır. Cortines ve ark.…”
Section: Discussionunclassified
“…The circumstances of premature birth can result in structural anomalies of the enamel of the primary dentition, as evidenced by a number of publications [22,44,[54][55][56][57][58][59][60][61][62]. The results of these studies are summarized in Table 1.…”
Section: Structural Defects Of the Primary Dentitionmentioning
confidence: 99%
“…Structural defects of both the primary and the permanent dentition imply an increased risk of caries and aesthetic problems. Furthermore, the associated increase in dental sensitivity has a negative impact upon the quality of life of the patient, which in turn can result in worsened oral hygiene [54,65]. A systematic review conducted by Jacobsen et al [69] concluded that there is a relationship between premature delivery and structural enamel defects of the primary dentition -with hypoplasia being the most common alteration.…”
Section: Structural Defects Of the Primary Dentitionmentioning
confidence: 99%